2015
DOI: 10.1002/qj.2691
|View full text |Cite
|
Sign up to set email alerts
|

Validation of eight atmospheric reanalyses in the Antarctic Peninsula region

Abstract: Eight atmospheric reanalyses were compared against observed vertical profiles of temperature, specific humidity and wind speed collected by two research aircraft in February-March 2010 in the Antarctic Peninsula region. These data offered a rare possibility to validate reanalyses against independent in-situ data which have not been assimilated into the reanalyses. The reanalyses had generally too moist profiles with too low wind speeds, but otherwise the errors in the reanalyses had large spatial differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…However, ERA-Interim does suffer from some prominent biases, including a significant warm bias of up to +1.4 K compared with the Aranda soundings. This low-level warm bias in ERA-Interim is consistent with findings in more recent data from the eastern side of the Antarctic peninsula (Nygård et al, 2016) and also with data from the Arctic Jakobson et al, 2012;Liu et al, 2008;Lüpkes et al, 2010;Wesslén et al, 2014). Corresponding to this warm bias, there is a significant moist bias in the lowermost layers of the reanalyses, when compared against the Aranda soundings and, to a lesser degree, the Fedorov soundings.…”
Section: Discussionsupporting
confidence: 89%
“…However, ERA-Interim does suffer from some prominent biases, including a significant warm bias of up to +1.4 K compared with the Aranda soundings. This low-level warm bias in ERA-Interim is consistent with findings in more recent data from the eastern side of the Antarctic peninsula (Nygård et al, 2016) and also with data from the Arctic Jakobson et al, 2012;Liu et al, 2008;Lüpkes et al, 2010;Wesslén et al, 2014). Corresponding to this warm bias, there is a significant moist bias in the lowermost layers of the reanalyses, when compared against the Aranda soundings and, to a lesser degree, the Fedorov soundings.…”
Section: Discussionsupporting
confidence: 89%
“…Here we show that geothermal heating-induced anomalies do extend toward the surface (thus impacting surface water mass transformation), particularly in polar regions where approximated atmospheric forcing errors can be substantial (e.g., Nygard et al 2016;Hobbs et al 2016). In an ocean-ice model, the approximated forcing components have their own errors distinct from the model that can enhance or compete with the model errors, with no clear way to separate the two error types (cf.…”
Section: A Model Featuresmentioning
confidence: 93%
“…In terms of specific weaknesses a number of studies have identified spurious trends in reanalyses in the temperature (Huai et al, ; Wang et al, ; Zhang et al, ), pressure (Bromwich & Fogt, ; Schneider & Fogt, ), precipitation (Bromwich et al, ; Nicolas & Bromwich, ), and surface wind (Bromwich et al, ; Nygard et al, ) fields around the Antarctic. Wohland et al () also questioned the quality of reanalyses surface wind trends in centennial reanalyses and Thorne and Vose () have questioned the reliability of long‐term trends in atmospheric reanalyses more widely.…”
Section: Introductionmentioning
confidence: 99%
“…Though they also see a lower wind variability in the reanalyses relative to AWS data which they attribute to smoothed topography. Nygard et al () examined eight reanalyses around the Antarctic Peninsula relative to field observations and found that wind speeds were predominantly low biased. Work in Jones et al () compared AWS wind speeds to four reanalysis products in the Amundsen Sea Embayment.…”
Section: Introductionmentioning
confidence: 99%